Enantioselective 1,3-Dipolar Cycloaddition Reaction of Nitrones with α-(Acyloxy)acroleins Catalyzed by Dipeptide-Derived Chiral Tri- or Diammonium Salts - Kidou, Chihiro; Mizoguchi, Haruki; Nehira, Tatsuo; Sakakura, Akira (Synlett, 2019)
Organoammonium salts of dipeptide-derived chiral triamines or diamines with TfOH catalyzed the enantioselective 1,3-dipolar cycloaddition reactions of α-acyloxyacroleins with nitrones to give the corresponding adducts in good yields (up to 96%) and with high diastereo- and enantioselectivities (up to 89% ee). Although α-(p-methoxybenzoyloxy)acrolein is rather unstable under the reaction conditions, α-(3-pyrroline-1-carbonyloxy)acrolein is stable enough to be smoothly converted into the corresponding adducts with the aid of the chiral organoammonium salt catalysts.
Keywords: acyloxyacroleins; 1,3-dipolar cycloaddition; isoxazolidines; nitrones; organocatalysis; asymmetric catalysis